Investment Valuation with Tax-optimized Financing Decisions and a Tax-optimized Default Alternative - Jochen Hundsdoerfer; Lutz Kruschwitz; Daniela Lorenz (BuR - Business Research, 2008)
In this paper we evaluate an indivisible investment project that is carried out in a corporation under very simple premises. In particular, we discuss a one-period model with certainty, the pure domestic case and proportional tax rates. Surprisingly, the decision problem turns out to be rather complex if one has to make allowance for different taxation of the corporation and its owner. Altogether there are more than 10 cases that have to be distinguished if the firm's managers want to make a correct decision, depending on the relation of personal and corporate tax rates.
urn:nbn:de:0009-20-13900
Keywords: 650; dividend distribution decisions; financing policy; investment decisions; payout policy; tax planning; Investitionsrechnung; Bilanzielle Bewertung; Körperschaftsteuer; Operations Research; Deutschland